EPHRIN-B1 Mosaicism Drives Cell Segregation in Craniofrontonasal Syndrome hiPSC-Derived Neuroepithelial Cells - Terren K. Niethamer; Andrew R. Larson; Audrey K. O’Neill; Marina Bershteyn; Edward C. Hsiao; Ophir D. Klein; Jason H. Pomerantz; Jeffrey O. Bush (Stem Cell Reports, 2017)
Although human induced pluripotent stem cells (hiPSCs) hold great potential for the study of human diseases affecting disparate cell types, they have been underutilized in seeking mechanistic insights into the pathogenesis of congenital craniofacial disorders. Craniofrontonasal syndrome (CFNS) is a rare X-linked disorder caused by mutations in EFNB1 and characterized by craniofacial, skeletal, and neurological anomalies. Heterozygous females are more severely affected than hemizygous males, a phenomenon termed cellular interference that involves mosaicism for EPHRIN-B1 function. Although the mechanistic basis for cellular interference in CFNS has been hypothesized to involve Eph/ephrin-mediated cell segregation, no direct evidence for this has been demonstrated. Here, by generating hiPSCs from CFNS patients, we demonstrate that mosaicism for EPHRIN-B1 expression induced by random X inactivation in heterozygous females results in robust cell segregation in human neuroepithelial cells, thus supplying experimental evidence that Eph/ephrin-mediated cell segregation is relevant to pathogenesis in human CFNS patients.